EFFECT OF FOOT MASSAGE ON RELAXATION AND PAIN INTENSITY OF CANCER PATIENTS - Nadjafi Ghezeljeh, T; Rahimiha, F; Mohaddes Ardebili, F; Hosseini, F (Iran University of Medical Sciences, 2002)
Background: Pain reduction is one of the main interventions in nursing care of cancer patient and foot massage is one of the complementary measures that decreases pain intensity and provides relaxation for patient. Objective: To determine the effect of foot massage on relaxation and pain intensity in hospitalized women with cancer. Design: This was a cross over clinical trial study in which each subject was in foot massage group 1 and 2, and also in controlled condition during 3 days. Relaxation, heart rate, and pain intensity were measured before and after 10 minutes of massage and recorded, and in control sessions patients lied on their beds comfortably for 20-30 minutes then their heart rate, pain intensity and relaxation were measured and recorded. Sample: 75 women with cancer, all over 18 years old, selected sequentially, and assigned for each session with random allocation. Result: There were a statistically significant differences on relaxation, pain intensity (p< 0/0001) and heart rate between subjects with foot massage (1) and without massage and between subjects with foot massage (1) and (2). In other word, massage decreased heart rate and pain intensity and increased relaxation. Repeated foot massage provided increased relaxation, and more reduction took place in heart rate and pain intensity. There were also statistically significant differences in variables trends of change (p<0/0001). In other word, from control to massage session (2), relaxation increased and heart rate and pain intensity decreased. Conclusion: According to the research findings, nurses can include foot massage in their daily care of cancer patients for pain reduction. They can provide proper education about foot massage for patients and their families. It is suggested that similar research in men and patients with chronic illnesses be done, and effects of long and intermediate time of massage be studied. A qualitative research for evaluating patient's feelings about massage and their experiences is recommended.